2013
DOI: 10.1177/1934578x1300800215
|View full text |Cite
|
Sign up to set email alerts
|

New Anthraquinone Derivatives from Geosmithia lavendula

Abstract: A phytochemical study of Geosmithia lavendula Pitt led to the isolation of three new anthraquinones: 1-acetyl-2,4,6,8-tetrahydroxy-9,10-anthraquinone (1), 2-acetyl-1,4,5,7-tetrahydroxy-9,10-anthraquinone (2), and 1-acetyl-2,4,5,6,7-pentahydroxy-9,10-anthraquinone (3), as well as another new compound named didodecyl thiodipropionate (propionic acid, 3,3-sulfinyl di-1,1′-didodecyl ester) (4), along with ten known compounds: 1-acetyl-2,4,5,7-tetrahydroxy-9,10-anthraquinone (rhodolamprometrin) (5), 1-acetyl-2,4,5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…The molecular formula of Compound I was determined to be C 15 H 10 O 7, based on HR-ESI-MS (m/z 315.0503 [M+H] + ) (Figs 8C and S16 ). Analysis of the 1 H ( S17 Fig ) and 13 C NMR spectroscopic data ( S18 Fig , S6 Table ) for compound I showed that its structure was consistent with that of 1-acetyl-2,4,6,8-tetrahydroxy-9,10-anthraquinone [ 25 ], indicating that compound I was an anthraquinone derivative. As we were unable to identify a PKS2-derived SM in A .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular formula of Compound I was determined to be C 15 H 10 O 7, based on HR-ESI-MS (m/z 315.0503 [M+H] + ) (Figs 8C and S16 ). Analysis of the 1 H ( S17 Fig ) and 13 C NMR spectroscopic data ( S18 Fig , S6 Table ) for compound I showed that its structure was consistent with that of 1-acetyl-2,4,6,8-tetrahydroxy-9,10-anthraquinone [ 25 ], indicating that compound I was an anthraquinone derivative. As we were unable to identify a PKS2-derived SM in A .…”
Section: Resultsmentioning
confidence: 99%
“…Anthraquinone derivatives have been found in the fungus G . lavendula [ 25 ]. Here we found that M .…”
Section: Discussionmentioning
confidence: 99%
“…The former is a compound with potential antibacterial, antibiofilm, and anti-inflammatory activities found in a sea anemone ( Stichodactyla haddoni ) [ 73 ] and sea hares ( Aplysia sp.) [ 74 ], while the latter is an antioxidant [ 75 ] that has been isolated from the fungi Geosmithia lavendulan [ 76 ]. None of the remaining aMFs listed in Table 2 have previously been reported to occur in sponges or marine samples, nor do they have any known biological function.…”
Section: Resultsmentioning
confidence: 99%
“…langdonii and G . levendula produce bioactive compounds with antimicrobial and antileishmanial activities (Stodulkova et al ., 2010; Malaka et al ., 2013). Several species of Geosmithia can also inhibit phoretic mites (Machingambi et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…from Ulmus minor afflicted with Dutch elm disease in Switzerland, although their role was not described (Hänzi et al, 2016). Furthermore, G. langdonii and G. levendula produce bioactive compounds with antimicrobial and antileishmanial activities (Stodulkova et al, 2010;Malaka et al, 2013). Several species of Geosmithia can also inhibit phoretic mites (Machingambi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%